2017
DOI: 10.1158/1538-7445.am2017-774
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 774: Notch pathway activation predicts resistance to bevacizumab therapy in glioblastoma

Abstract: Glioblastoma, the most common adult glioma, is associated with a dismal prognosis. Treatment with bevacizumab has not significantly prolonged overall patient survival times. Glioblastoma resistance to angiogenesis inhibitors is attributed to multiple interacting mechanisms. We have thus embarked on a comprehensive effort to detecting expression signatures that are associated with response to the therapy and these signatures may allow prospective selection of patients with high likelihood of responding to thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nonetheless, NICD is widely acknowledged as an important marker of Notch pathway activation, which indicates that SPOPL could regulate the Notch signaling pathway in GSCs. There is extensive evidence that the Notch signaling pathway plays an important role in the regulation of cellular fate, proliferation, and migration, as well as in the maintenance of the resting state of the cell and in regulating the differentiation of neural stem cells (NSCs) [31]. Emerging evidence suggests that the extracellular matrix protein Tenascin-C can activate the Notch signaling pathway in GSCs [32].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, NICD is widely acknowledged as an important marker of Notch pathway activation, which indicates that SPOPL could regulate the Notch signaling pathway in GSCs. There is extensive evidence that the Notch signaling pathway plays an important role in the regulation of cellular fate, proliferation, and migration, as well as in the maintenance of the resting state of the cell and in regulating the differentiation of neural stem cells (NSCs) [31]. Emerging evidence suggests that the extracellular matrix protein Tenascin-C can activate the Notch signaling pathway in GSCs [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously confirmed that the Notch signaling pathway is critically associated with stem cell fate determination, proliferation, maintenance of cell quiescence, metastasis, and modulation of differentiation of both normal NSCs and GSCs ( 124 ). Via mutual effects with ligands on a considerable number of cells, the Notch pathway, including the four Notch receptors (Notch 1–Notch 4) and five ligands (Jagged-1 and Jagged-2, and Delta-like-1, Delta-like-3, and Delta-like-4), can regulate the interaction between cells and neighboring cells covering a short range ( 125 , 126 ).…”
Section: Direct Targeting Of Gscsmentioning
confidence: 91%
“…Notch pathway is important for determination of cell fate, proliferation, maintenance of cell quiescence, migration and regulate neural stem cell differentiation [134]. It starts by activation of γ-secretase by the jagged family ligands which leads to cleavage of notch receptors, then the intracellular notch receptor domain (NICD) translocates to the nucleus and formation of recombination signal binding protein for immunoglobulin kappa J region (RBPJ) and Mastermind-like 1 (MAML) complexes in the nucleus and activation of the hairy and enhancer of split (HES) and HEY genes that maintain multi-potency [135] (Figure 7).…”
Section: Notch Signalling Pathwaymentioning
confidence: 99%